Clinico-pathological profile, radiological presentation and drug susceptibility pattern of new smear positive (category I) pulmonary tuberculosis: a single centre experience in Delhi, India - Moitra, Saibal; Sen, Sukanta; Das, Prasanta; Bose, Mridula (International Journal of Research in Medical Sciences, 2017)
Background:Aim of current study was to determine the clinical characteristics, radiological, laboratory features and anti-tubercular drug sensitivity in new smear positive (category I) pulmonary tuberculosis cases in a tertiary care dedicated TB OPD, Delhi. Methods:The study was a cross-sectional observational study and consists of 100 cases of new smear positive pulmonary tuberculosis cases (category I) irrespective of age and sex. The sputum were collected, stained with Ziehl-Nielsen (Z-N) staining and ultimately inoculated on Lowenstein-Jensen (L-J) media for six weeks. All sputum smear positive cases were subjected to culture and drug-susceptibility testing by 1% proportion method on Lowenstein-Jensen (LJ) medium. The Drug-Susceptibility Testing (DST) for isoniazid (INH), rifampicin (R-cin), ethambutol (EMB) and streptomycin (SM) were performed. Results:The age & sex distribution of 100 patients showed that majority of the patients (79%) belonged to 2nd, 3rd and 4th decades & 60 % were males and 40% were female with male to female ratio 3:2 respectively. Cough (83%), fever (77%) and weight loss (76%) were the most common presenting clinical features. The chest X-ray of 100 smear positive patients showed that 53% of patients had evidence of 35% unilateral and 18% bilateral consolidation and 46% had cavitary lesions on chest X-ray (PA view) with 37% and 9% of patients having unilateral and bilateral cavities respectively. Of these 82 culture positives, 56.1% (n=46) were susceptible to all first-line anti-tubercular drugs, while 43.9% (n=36) were resistant to mostly one or other anti-tubercular drugs (INH, R-cin, SM or EMB). Conclusion: We stressed the importance of early diagnosis of new cases by clinico-pathological features, identifying of drug resistance trends in anti-tubercular treatment naïve patients, in order to assess the efficacy of current interventions. Overall, these findings emphasize the importance of early diagnosis of drug resistance pattern of M. tuberculosis isolates to anti-tubercular in category I patients as well as its association with HIV across the country to timely modify and strengthen the national programs in order to prevent the emergence of MDR-TB strains and avert the threat of XDR-TB.